High nutrition risk related to dietary intake is associated with an increased risk of hospitalisation and mortality for older Māori: LiLACS NZ - Sylvia M. North; Carol A. Wham; Ruth Teh; Simon A. Moyes; Anna Rolleston; Ngaire Kerse (Elsevier, 2018)
Abstract Objectives: To investigate the association between domains of nutrition risk with hospitalisations and mortality for New Zealand Māori and non‐Māori in advanced age. Methods: Within LiLACS NZ, 256 Māori and 399 non‐Māori octogenarians were assessed for nutrition risk using the Seniors in the Community: Risk Evaluation for Eating and Nutrition (SCREEN II) questionnaire according to three domains of risk. Sociodemographic and health characteristics were established. Five years from inception, survival analyses examined associations between nutrition risk from the three domains of SCREEN II with all‐cause hospital admissions and mortality. Results: For Māori but not non‐Māori, lower nutrition risk in the Dietary Intake domain was associated with reduced hospitalisations and mortality (Hazard Ratios [HR] [95%CI] 0.97 [0.95-0.99], p=0.009 and 0.91 [0.86-0.98], p=0.005, respectively). The 'Factors Affecting Intake' domain was associated with mortality (HR, [95%CI] 0.94 [0.89-1.00], p=0.048), adjusted for age, gender, socioeconomic deprivation, education, previous hospital admissions, comorbidities and activities of daily living. Conclusion: Improved dietary adequacy may reduce poor outcomes for older Māori. Implications for public health: Nutrition risk among older Māori is identifiable and treatable. Effort is needed to engage relevant community and whānau (family) support to ensure older Māori have food security and cultural food practices are met.